Mapping Intellectual Structures and Research Hotspots of Triple Negative Breast Cancer: A Bibliometric Analysis - Hao, Kai-jun; Jia, Xiao; Dai, Wen-ting; Huo, Ze-min; Zhang, Hua-qiang; Liu, Jing-wei; Wang, Xiao-bing (Frontiers in Oncology, 2022)
Background: Triple negative breast cancer (TNBC) is a highly heterogeneous breast cancer subtype with a poor prognosis due to its extremely aggressive nature and lack of effective treatment options. However, there is no bibliometric study on TNBC. This study aims to summarize the current hotspots of TNBC research and evaluate the TNBC research trends, both qualitatively and quantitatively through bibliometric analysis tools, to provide valuable references for further study in this field. Methods: Scientific publications of TNBC-related studies from January 1, 2010, to October 17, 2020, were obtained from the Web of Science database. The Bibliographic Items Co-occurrence Matrix Builder software was used to obtain the high-frequency keywords layout. Subsequently, a binary matrix of word-paper and co-word matrix was formulated. gCLUTO was used for double clustering and visualization analysis of the high-frequency keywords and BibExcel was used to build strategic coordinates. A series of other knowledge maps related to this field were analyzed and visualized by CiteSpace 5.7.R1 and VOSviewer 1.6.15 software. Results: A total of 12,429 articles related to TNBC were identified. Among them, Lehmann BD (2011) had the greatest academic influence. Fong PC (2009) bridged the different knowledge fields and currently serves as a landmark reference for the TNBC research field. Eight research hotspots of TNBC were identified by co-word analysis. A strategic diagram was used to reveal the relationships among various clusters, research prospects, intellectual bases, and research fronts. Conclusion: Herein, we summarized the last ten years of published literature on TNBC and analyzed its aspects, including the publication information regarding authors, years of publication, countries, and subsidiary organs. In the core hotspots, research on neoadjuvant chemotherapy, paclitaxel therapy, and molecular typing of TNBC is relatively mature compared to research on TNBC immunotherapy, poly-ADP-ribose polymerase inhibitors, and other targeted therapies. Additionally, research on tumor cell migration and TNBC proteins and receptors is still popular and will continue to remain at the forefront soon.